Framing the New Role of Information Professionals: investigating Copyright Literacy Levels and Awareness of Academic Librarians in Pakistan. Issue 1 (2nd January 2022) - Nawazish, Mehwish; Batool, Syeda Hina
Abstract: Modern and fast ways of information reproduction affect the social norms and moral responsibilities of citizens. Nowadays libraries are continuously facing the problem of maintaining the balance between providing information access and whilst also protecting authors' rights. The recent and emerging phenomenon of misinformation and disinformation have heightened the need to be informed about authentic information and their owners' rights. This has resulted in a requirement for information professionals to know, understand and practice copyright law. A cross-sectional survey was carried out to investigate the level of awareness/knowledge and perceptions and practices of copyright legislation by information professionals in Pakistan. The findings reveal that a large number of respondents were moderately aware of Intellectual Property Rights.